(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2021)
The symbolic values behind the art in the animistic practices among the Tharus of Dang and Deukhuri is a paper that deals with various symbolic objects, that are termed as fetish associated with the animistic practices observed by the Tharus of Dang and Deukhuri of Terai Nepal. The objects or the fetish created by them when analyzed through an artistic perspective, seems, to the outsiders or through the ‘Etic Approach’ just a local ethnic crude handicraft. However, when analyzed through the ‘Emic Approach’ these artistic creations or fetish have great symbolic values associated with it. This paper-based on a field survey of the two regions has brought to limelight the symbolic values behind artistic creativity associated with their animistic practices.